AGAMA SIAP SAJI DI KALANGAN MILLENIAL - Wardah Wardah (Muẚṣarah: Jurnal Kajian Islam Kontemporer, 2020)
AbstractMillennial comes from English, Millennium which means a thousand years. Millennials are described as a generation that cannot be far from technology users including "You Tube" and "Instagram" social media. The development of technology is now increasing, information is becoming more easily known including in studying theology. Problems that often occur, religion that is presented instantaneously through these two media gives more positive and negative implications, in one side of the media it provides an alternative as a means of knowledge of religion, but on the other hand the media provides a superficial understanding of religion as a whole. According to the Republika Data Center from the Ministry of Communication and Information in Indonesia, a number of adolescents are so aggressive in consuming streaming video entertainment and religious content. Ericson noted that in 2011 around 7% of teens between the ages of 16-19 years watched a lot of videos through You Tube. At this time the business is to consume the internet for 18 hours a day. From these data it is interesting to study the religious studies obtained by the millennials from Instagram and You Tube accounts. The focus of this research is to know in comprehensively and in-depth the practical religion of the millennials from the influence of social media, Instagram and You Tube. The researcher conducted interviews with UIN Antasari Banjarmasin students from five faculties represented by each faculty totaling two people. Sampling uses purposive sampling method. This study aims to add understanding in taking a wise attitude to address the phenomenon of understanding religion instantly. The research method used is qualitative, the technique of data collection is done in triangulation, a combination of observation, interviews and documentation. The results of this qualitative study are to understand the uniqueness in constructing the phenomenon and the results of virtual da'wah containing scriptural content−those who understand religion without interpretation−because it refers to the Qur'an and hadith in text an sich). In addition, it also concludes that there is a hybridization of religious identity in the millennials. Therefore, this study provides recommendations that are expected to grow the awareness of the millennial generation so that understanding religion must be comprehensive and do not always make instant things a source of consumption for their religious studies.AbstrakMillenial berasal dari bahasa Inggris, Millennium yang berarti masa seribu tahun. Millenial digambarkan sebagai generasi yang sangat lekat dengan penggunaan media  sosia1  “You  Tube“  dan  “Instagram“. Perkembangan  teknologi  kini  semakin  meningkat,  informasi  semakin  mudah  diketahui  termasuk  dalam mengkaji  ilmu  agama.  Permasalahan  yang  kerap  terjadi,  agama  yang  disajikan  secara  instan  melalui  kedua media tersebut sedikit banyak memberikan implikasi positif dan negatif, dalam salah satu sisi media tersebut memberikan   alternatif   sebagai   sarana   pengetahuan   ilmu   agama,   namun   di   sisi   lain     media   tersebut memberikan  pemahaman  yang  dangkal  terhadap  agama  secara  utuh.  Menurut  Pusat  Data  Republika  dari Kementerian  Kominfo  di  Indonesia,  sejumlah  remaja  begitu  gencar  dalam  mengkonsumsi  streaming  video hiburan maupun konten agama. Ericson mencatat pada tahun 2011 silam sekitar 7% remaja antar usia 16-19 tahun banyak menonton video melalui You Tube. Pada saat ini urusan untuk mengkonsumsi internet selama 18 jam dalam sehari. Dari data tersebut menarik untuk diteliti mengenai kajian rkeagamaan yang didapat para millenial dari akun Instagram dan You Tube. Fokus penelitian ini adalah mengetahui secara komprehensif dan mendalam  bagaimana  keagamaan  praktis  dari  para  millenial  dari  pengaruh  sosial  media  Instagram  dan  You Tube.  Peneliti  melakukan  wawancara  kepada  mahasiswa  UIN  Antasari  Banjarmasin  dari  lima  fakultas  yang diwakili  setiap  fakultasnya  berjumlah  dua  orang.  Pengambilan  sampel  menggunakan  metode   purpossive sampling.  Penelitian  ini  bertujuan  untuk  menambahkan  pemahaman  dalam  mengambil  sikap  bijak  untuk menyikapi  fenomena  memahami  agama  secara  instan.  Metode  penelitian  yang  digunakan  adalah  kualitatif, teknik pengumpulan data dilakukan secara triangulasi, gabungan observasi, wawancara dan dokumentasi. Hasil penelitian  kualitatif  ini  adalah  untuk  memahami  keunikan  dalam  mengkonstruksi  fenomena  dan  hasilnya dakwah  virtual  yang  berisi konten  yang  bersifat  skriptual—yang memahami  agama  tanpa  interpretasi—karena merujuk al-Qur’an dan hadis secara teks an sich). Selain itu juga secara kesimpulan muncul gerakan hibridasi identitas keagamaan di kalangan millenial. Oleh karena itu, penelitian ini memberikan rekomendasi yaitu diharapkan tumbuh kesadaran generasi millenial agar dalam memahami agama haruslah komprehensif dan tidak selalu menjadikan hal yang instan sebagai sumber konsumsi rujukan studi agama mereka.